Penerapan Model Pembelajaran Learning Cycle 5E Untuk Meningkatkan Sikap Ilmiah Dan Hasil Belajar Biologi Siswa Kelas XI IPA 4 SMA Negeri 5 Pekanbaru - Irda Sayuti; Rosmaini S; Sri Andayannhi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
This study was aimed to improve the scientific attitudes andlearning outcomes of students in learning Biology by applying the “5ELearning Cycle”teaching modelinXIScience 4 class of SMAN 5 Pekanbaruin the academic year of 2011/2012. The study was conducted from Septemberto October2011. The subjects of the research were the students of XI Science4 class of SMAN 5 Pekanbaru, totaling 39 people. The parameters measuredwere the students’ scientific attitudes, students’ learning outcomes, students’and teacher’sactivities. In the first cycle the average of students’ scientificattitudeswas69.73% (Fair), and it wasincreasedin the second cycle up to84.75% (Good). Moreover, the students’ capability in comprehending thematerials givenin the first cyclewas76.95 (Less), and it was increased upto82.90in the second cycle (Enough).On the other side, the students’mastery,seeing from their post-testin the first cyclewas64.11% (Mastering)and35.89% (Not Mastering), and it was increasedin the second cycletobe84.61%(Mastering) and15.39% (Not Mastering). The activitiesof1studentsin the first cyclewas63.01% (Fair), and it wasincreasedin the secondcycleup to81.94% (Good). All of the teachers’ activitiesin the firstcyclewiththeaverage of 91.67% (Good) increasedin the second cycletobe100% (Excellent). Therefore, it can be concluded from this research thatthe application of5ELearning Cycleteaching model was successfullyimprovedthe scientific attitudes and learning out comes of studentsin learningBiology at XIScience 4 of SMAN 5Pekanbaruin the academic yearof2011/2012.